Differences in the Structure and Diversity of Invertebrate Assemblages Harbored by an Intertidal Ecosystem Engineer between Urban and Non-Urban Shores - Ana Catarina Torres; Marcos Rubal; Ricardo Costa-Garcia; Isabel Sousa-Pinto; Puri Veiga (Journal of Marine Science and Engineering, 2022)
Nowadays, coastal urbanization is one of the most serious and prevalent pressures on marine ecosystems, impacting their biodiversity. The objective of this study was to explore differences in attributes and biodiversity associated with an intertidal ecosystem engineer, the mussel Mytilus galloprovincialis Lamarck, 1819 between urban and non-urban shores. For this, mussel attributes and their associated macrofauna were compared between urban and non-urban rocky shores in the north of Portugal. Results showed that the largest sized mussels were more frequent on urban shores, whereas the smallest size class was only present in non-urban shores. Regarding macrofauna associated with mussels, the number of taxa was significantly higher on non-urban shores. Moreover, the structure of the macrobenhic assemblages was significantly different between urban and non-urban shores. Most important taxa responsible for differences were more abundant on non-urban shores except for Nucella lapillus, Idotea pelagica and Oligochaeta that were more abundant on urban shores. Therefore, our results showed that the mussel size frequency and the structure of the associated macrobenthic assemblages changed in urban shores. Considering the relevance of mussel beds for biodiversity and human well-being, our results indicate the need of adopting proper management plans to minimize these effects on urban intertidal ecosystems.